ANALISIS TINDAKAN SOSIAL DALAM PERISTIWA PENOLAKAN VAKSIN - Sugiyono, Paulus Bagus (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The purpose of this article is to analyze the phenomenon of Covid-19 vaccine rejection among Indonesia society which occurred in the midst of Covid-19 pandemic. This research uses qualitative approach by employing secondary data related to the phenomenon of Covid-19 vaccine rejection. This article itself brings the concept of social action offered by Max Weber as a conceptual framework. The main finding of this research is that there are various reasons behind the phenomenon of Covid-19 vaccine rejection. Those reasons portray the rich variety of meanings which also mean that there are many socio-cultural contexts behind it. Therefore, we need the appropriate strategy to face such phenomenon. Thus, the goals of Covid-19 vaccine promotion could be reached well.